Disturbance of Ecological Self and Impairment of Affordance Perception - Kim, Nam-Gyoon; Effken, Judith A. (Frontiers in Psychology, 2022)
Affordance, a radical concept James Gibson introduced in the 1970s, remains controversial today. Defined as environmental properties taken with reference to an animal’s anatomy and action capabilities, affordances are opportunities for action the environment offers. By perceiving affordances, organisms hold meaningful relationships with their surroundings. Affordance is not just a theoretical concept but, as the embodiment of meanings and values, has serious psychological implications. We contend that the lack of these meanings and values underlies the irrational behavior seen in patients with self disorders such as schizophrenia. We reason that it is by perceiving affordances that individuals keep in touch with their surroundings and stay mentally healthy. Using contrapositive reasoning, the reverse could also be true. That is, when individuals experience difficulty maintaining meaningful relations with their surroundings and suffer from mental health problems, we might anticipate that their affordance detection systems are impaired. In two studies conducted in our laboratory, patients with schizophrenia and Alzheimer’s disease were shown to have impaired capacity to perceive affordances, a result qualifying as contra-positive evidence corroborating the affordance concept. In addition, our results provide support for accepting contra-positive evidence as a complementary tool to positive evidence for empirically validating concepts such as affordance and meaning.